1976
DOI: 10.1103/physrevlett.37.645
|View full text |Cite
|
Sign up to set email alerts
|

I=32 πNResonances in the 1900-MeV Region

Abstract: We report results of a TTN partial-wave analysis for I =| resonances observed in the 1900-MeV region: ^3 5 (1885), F 37 (1945), P 31 (1940), and D 35 (1925). The D 35 (1925) is difficult to accommodate in conventional baryon models; we discuss an alternative model having such a state.The SU(6)xO(3) harmonic-oscillator model proposed by Greenberg, 1 its relativistic 2 and diquark 3 variations, and recent "dual string" 4 and "bag" 5 models have had notable success in reproducing the observed baryon mass spectru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…There are works on this state by Cutkosky and Hendrick 23) and Bowler et al, 24) where the possibility of a quark-gluon hybrid state is discussed. §4.…”
Section: ∆(1930)mentioning
confidence: 99%
“…There are works on this state by Cutkosky and Hendrick 23) and Bowler et al, 24) where the possibility of a quark-gluon hybrid state is discussed. §4.…”
Section: ∆(1930)mentioning
confidence: 99%
“…Due to difficulties in reproducing some helicity amplitudes relative to 7-decay, it has been suggested that some low energy states such as the Roper resonance (again) or the states P~ at 1710MeV and PJ3 at 1730 MeV be hybrid states [9]. Such an explanation has also been suggested for the state A (5/2-) at 1930 MeV which is relatively quite low in energy [ 10].…”
Section: Introductionmentioning
confidence: 98%
“…3 A. i+-mr d&1 + 2(pt)p 31 (P') (A14) Thus, in the absence of crossing symmetry, the = (1+f '~m ')+LMM' (&) This result can also be derived by comparing the inverse problem for v'(p) in the potential model of Ref. 2 with the Chew-Low inverse problem developed here.…”
Section: Inverse Problem and Approximationmentioning
confidence: 81%
“…It is possible to completely eliminate the multimeson matrix elements which appear explicitly in (2.2) (11,13 and 31,33), (2,9) wl (2.13) known dependence on p and p' and one having a complicated dependen. ce on co, (p~T( )~p)= "" , ""'.…”
Section: Derivation Of Equationsmentioning
confidence: 99%